Kritik Abdul Karim Amrullah terhadap Rābiṭah di Minangkabau dalam Tafsir al-Burhān - Helfi Helfi (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2018)
This article explores the thought of Abdul Karim Amrullah on the issue of rābiṭah in Minangkabau. He is regarded as very critical in responding social and cultural life, especially relating to tarekat. All behaviors of society should have basis from the Qur'ān and Sunnah. All acts which are not based on the Qur'ān and Sunnah are considered as innovation (bid'ah) that should be avoided. Amrullah categorically rejected rābiṭah for there was no sharī'ah basis for it, although the kaum tua (conservative) in Minangkabau attempted to conserve rābiṭah in their surau. Rābiṭah as one of wasīlah (mediator) is understood as a medium to reach God through substitute face. What is meant is the murshid who taught their followers to achieve the determined position in their own tarekat. Amrullah's criticism towards rābiṭah in Minangkabau initially resulted in resistance, especially among the founder of tarekat. However, in the course of time, the issue of tarekat declined and even underwent significant decay in Minangkabau.